A questionnaire-based study on quality and adequacy of clinical communication between physician and family members of admitted Covid-19 patients. Issue 2 (February 2022) - Rahul; Kumar, Anup; Verma, Alka; Sanjeev, Om Prakash; Singh, Ratender Kumar; Ghatak, Tanmoy; Nath, Alok
Abstract: Objective: To assess adequacy of present means of clinical communication between physicians and (Covid-19) patients' family members, to analyse their perspectives and recommend felicitous practices for virtual conversation during ongoing pandemic. Methods: Cross-sectional questionnaire-based (20 questions) anonymous online survey was conducted including patient's relatives (Group-1) and treating physicians (Group-2), through Google Forms. Results: Response Rate was 82.5%. Group-1 and Group-2 included 155 and 204 respondents respectively. Group-1 preferred update by resident doctors (39%), twice a day (41.9%), daily case-summaries (80%) and hand-written document/electronic messages (53%, 31%) as consent. Whereas Group-2 favored update by senior consultants (63%), daily one appraisal (55.9%) and scanned copies of hand written consent (81%) before high-risk procedures. The groups broadly agreed on the desired duration for a fruitful discussion (5–10 min) and designating one responsible person from the family for daily appraisal. Conclusion: Use of modern techniques/technologies of communication (voice/video calls, texts) during the ongoing pandemic is acceptable to majority. Practice implications: Study proposes a senior physician should communicate to a designated responsible family member at-least once a day for stable and twice a day for critical covid patients (more if patient's health condition changes), either by voice or video calls for 5–10 min.